Methodological constraints in interpreting serum paraoxonase-1 activity measurements: an example from a study in HIV-infected patients - Parra, Sandra (BioMed Central, 2010)
BACKGROUND: Paraoxonase-1 (PON1) is an antioxidant enzyme that attenuates the production of the monocyte chemoattractant protein-1 (MCP-1) in vitro. Although oxidation and inflammation are closely related processes, the association between PON1 and MCP-1 has not been completely characterised due, probably, to that the current use of synthetic substrates for PON1 measurement limits the interpretation of the data. In the present study, we explored the relationships between the circulating levels of PON1 and MCP-1 in human immunodeficiency virus-infected patients in relation to the multifunctional capabilities of PON1. METHODS: We measured selected variables in 227 patients and in a control group of 409 participants. Serum PON1 esterase and lactonase activities were measured as the rates of hydrolysis of paraoxon and of 5-(thiobutyl)-butyrolactone, respectively. Oxidised LDL and MCP-1 concentrations were determined by enzyme-linked immunosorbent assay. High-density lipoproteins cholesterol, apolipoprotein A-I, and C-reactive protein concentrations were measured by standard automated methods. RESULTS: There were significant relationships between PON1 activity and several indices of oxidation and inflammation in control subjects and in infected patients. However, these relationships varied not only with disease status but also on the type of substrate used for PON1 measurement. CONCLUSION: The present study is a cautionary tale highlighting that results of clinical studies on PON1 may vary depending on the methods used as well as the disease studied. Until more specific methods using physiologically-akin substrates are developed for PON1 measurement, we suggest the simultaneous employment of at least two different substrates in order to improve the reliability of the results obtained.